Natural conservation of guinea pig (Cavia porcellus) meat vacuum packed: Oregano essential oil effect on the physicochemical, microbiological and sensory characteristics - Moreno, Yamaly (2018)
Guinea pig meat is high in protein and low in fat, representing an attractive option for human nutrition. In addition, its sensory characteristics are making this product more appreciated in both internal and external markets. However, it is a highly perishable product, for which it is important to look for products and technologies that allow it to preserve its quality. Oregano essential oil is a natural product that presents antimicrobial and antioxidant properties that can use on the preservation of meat. Thus, the objective of this work was to study the effect of the concentration of oregano essential oil (0.5% and 1%) and storage time (0, 35 and 70 days) at -10 °C, on physicochemical, microbiological and sensory characteristics of guinea pig meat vacuum packed. For this was used guinea pigs of Peru race with 3 months of age-old and weight range between 600 and 700 g. Oregano essential oil at 0.5 and 1% was dissolved in a saline solution at 2%, next add to surface internal and external of meat after this was packing vacuum in PE pouches and stored at -10 °C until 35 and 70 days. At each storing time was evaluated physicochemical, microbiological and sensory characteristics. The best results in the majority of the characteristics were obtained to 0.5% oregano essential oil concentration and 70 days of storage, in this condition the characteristics were pH = 6.11 ± 0.05; moisture (%) = 71.6 ± 0.36; ΔEi = 3.74 ± 0.77; ΔEe = 8.30 ± 0.55; PBC = 99 ± 4 cfu/g and; texture, odor, internal and external color and, appearance acceptable.